Reemergence of Oropouche in the Brazilian Amazon: A phylodynamic and phylogenetic analysis - Karolaine Santos Teixeira; Hillquias Monteiro Moreira; Tárcio Peixoto Roca; Edilene Pereira Pimentel; Jackson Alves da Silva Queiroz; Jessiane Rodrigues Ribeiro; Ana Maisa Passos-Silva; Adrhyan Araújo; Kátia Ingred da Silva Maia; Felipe Gomes Naveca; Ighor Arantes; Gonzalo Bello; et al. (Travel Medicine and Infectious Disease)
Background: The distribution of arboviruses in endemic regions is experiencing a significant shift, along with the re-emergence of Oropouche virus (OROV) as a significant pathogen, characterized by dynamic vector-borne transmission. Despite growing public health relevance, OROV remains insufficiently characterized, with limited comprehensive genomic and epidemiological data. This knowledge gap affects the accuracy of diagnostic approaches and limits the effectiveness of surveillance and control strategies. This study aimed to characterize the re-emergence of OROV in endemic regions, elucidate its epidemiological distribution, and clarify the epidemiological distribution of OROV and assess its impact on diagnostic strategies and surveillance for acute febrile illness. Methods: Between January and July 2024, a total of 869 individuals with malaria-negative acute febrile illness were screened for dengue, Zika, and chikungunya viruses. Duplex RT-qPCR assays were subsequently employed to detect Mayaro and Oropouche viruses. Spatiotemporal and geospatial analyses were conducted to assess the distribution of OROV in relation to environmental factors. Findings: Among the participants, 35 % tested positive for OROV, with cases predominantly concentrated in forest and riverine areas. Considering that the significant increase in the number of cases occurred in a short space of time, the results highlight the urgent need to strengthen genomic and epidemiological surveillance to tackle emerging arboviral threats.